Tanzania : Do Campaigns to Get People to Wash Hands and Use (Improved) Toilets Work? - World Bank (World Bank, Washington, DC, 2016)
The World Bank is committed to providing opportunities for healthy child development, and ensuring safe sanitation and good hygiene is critical to achieving that. In Tanzania, the World Bank’s Water and Sanitation Partnership worked with the government to create and implement campaigns to improve sanitation and reduce illness among young children by encouraging handwashing and use of improved sanitation such as toilets. A randomized evaluation, built into the program, found that while open defecation was reduced, the handwashing campaign wasn’t successful at getting people to wash their hands with soap and water, and neither campaign led to meaningful health benefits, even when combined. The evidence reveals the difficulties of reducing diarrheal disease and the need for more research to identify successful strategies.